Hospital mortality in a highly complex center from Lambayeque-Peru, 2014-2018 - García-Ahumada, Félix (2020)
Objetive: To describe clinical characteristics and aspects of mortality in patients from the Hospital Regional Lambayeque during 2014-2018; Material and Methods: Retrospective and descriptive study with exploratory analysis. All deceased patients from the different services were included according to the Quality Management System registry. Results: There were 1560 deaths (4.7%); the median age was 55 years (IQR = 23-100), the most frequent age group was: over 75 years: 25.1%; 50.2% were women, 74.1% were from Lambayeque and 36.8% from Chiclayo; 32.6% were treated by Internal medicine and 18% by Intensive Medicine. The years that contributed with most deaths were: 2017 (21.2%) and 2014 (20.7%); the frequency of mortality was higher during 2014: 6.1% and lower during 2018: 4.1%. The most frequent discharge diagnoses were: sepsis/septic shock: 30.17% and respiratory failure:10.7%. In 14/1560 (0.9%) “cardiac arrest” appears as the final diagnosis and in 82/1560 (5.2%) the first diagnosis is “non-diagnosis”. In 14/1560 (0.9%) only signs or diagnoses that do not explain deaths are reported. Only in 44.6%, the second discharge diagnosis was recorded. Conclusions: The older adult group was the most frequent, with sepsis and respiratory failure, treated by internal medicine and intensive care; Mortality is high, but with decrease through the years. There are deficiencies in the registration of information both in quality and subreport.